Kosovar youth's conceptions of gender roles : academic girls and practical boys - Turunen, Tiia (2020)
Gender is a social construction and a result of socialization rather than a fixed feature of an individual, and gender roles are therefore also socially constructed. Kosovo is a poor, post-conflict country. Economic growth has a positive influence on a more equal society, which makes Kosovo an interesting context in which to study conceptions of gender. Albania has scored low on Gender Equality Scale (GES) (Weziak-Bialowolska, 2014) and due to the close cultural and geographical proximity the situation in Kosovo can be assumed to be similar. The aim of this study is to find out what Kosovar teenagers think of house-hold chores division and how should these be divided in their homes, and what kind of conceptions Kosovar teenagers have about their dream jobs? The data were gathered in Kosovo at local schools through a questionnaire, and it comprises 203 answers from Kosovar students between 10–15 years of age. The Finnish Liaison and Monitoring Team (LMT), of which the researcher was a member, conducted the questionnaire in the context of a Finnish peacekeeping mission in Kosovo. The data were analyzed using qualitative thematic analysis and problem –driven content analysis. The traditional gender roles reflect the reality in students’ homes, while most would like to have a more equal division of labour. Dream jobs are also mostly divided as expected between males and females. This study may help to understand the conceptions of gender socialization and how the conceptions of gender affect teenagers’ lives and life goals. Teachers and educators should be aware of the effect of gender roles on how children and adolescents see their abilities.